Comparison of nutritional status and growth curves of children and adolescents in the city of Goiânia, Goiás: cross-sectional study - Alves, Rafael Ribeiro; Baptista, Tadeu; Marques, Vitor Alves; Silva, Weder Alves da; Silva, Marcelo Henrique; Santos, Douglas de Assis Teles; Vieira, Carlos Alexandre (São Paulo Medical Journal, 2025)
BACKGROUND: Nutritional status and growth curves can affect cognitive development, increase the risk of infection, and contribute to the development of chronic diseases. Its etiology is related to food, socioeconomic, and maternal conditions. However, to date, no data on these parameters exist in the state of Goiás, Brazil. OBJECTIVE: To compare the nutritional status and growth curves of children and adolescents in the city of Goiânia, Goiás, Brazil. DESIGN AND SETTING: This was a cross-sectional study. A total of 529 individuals were recruited from a primary health center in the municipality. METHODS: To assess nutritional status, the sample was divided into three categories: 3–4, 5–10, and 11–19 years, with z-score classification considering body mass index for age. The classification of growth curves was performed considering the median height values for age, assuming two references: (a) young Brazilian population and (b) one recommended for international use. The independent sample T-test was used to compare anthropometric variables. RESULTS: The results showed that the classification of eutrophics represents a predominant percentage between both sexes (men: 03–04 = 55.4%; 05–10 = 57.6%; 11–19 = 53.5 % and women: 03–04 = 53.5%; 05–10 = 63.9%; 11–19 = 56.9%), and growth curves showed differences in specific periods in both sexes. CONCLUSIONS: It can be concluded that children and adolescents from the city of Goiânia present as predominance the eutrophic nutritional status, followed by the risk of overweight, underweight, obesity, and malnutrition of both sexes.